[Alchemical miscellany]
This manuscript is an important miscellany of practical and theoretical alchemical texts with a full-page drawing of alchemical instruments reflecting the activities of a fifteenth-century alchemist. The manuscript was written in Italy, probably Northern Italy, most likely in the third quarter of the fifteenth century, circa 1450-1475, based on the evidence of the script. Notably, at least part of the manuscript is a palimpsest (copied on previously used parchment, with the original script scraped and/or washed away). The manuscript also bears signs of being heavily used, especially on folios with practical recipes, which are remarkably soiled. The manuscript begins with an introductory statement and passage from Johannes de Rupescissa's De confectione veri lapidis and includes a warning that the pursuit of alchemy should not be governed by a desire for temporal things. The subsequent text includes a series of practical recipes and procedures for subliming mercury, making alcohol, and so forth, as well as several more philosophical passages reflecting a belief in alchemy to cure the ills of Christian society.
Keywords: Alchemy; Alchemy--Manuscripts; Johannes, de Rupescissa, approximately 1300-approximately 1365; Formulas, recipes, etc.